Antioxidant properties (components and capacity) in fresh, powder and fibre products prepared from bacang (Mangifera foetida) fruits - S. T., Tan; I., Amin (Nutrition Society of Malaysia, 2008)
Mangoes are a good source of dietary antioxidants such as ascorbic acid, carotenoids and phenolic compounds. This study was aimed at investigating the antioxidant capacity, total reducing activity, flavonoid, carotenoid and ascorbic acid contents of fresh mango, mango powder and mango fibre prepared from bacang (Mangifera foetida) fruits. The antioxidant capacities of the mango extracts were determined using Ferric Reducing Antioxidant Power (FRAP), Trolox Equivalent Antioxidant Capacity (TEAC) and β-carotene bleaching assays. One-way ANOVA and Turkey HSD tests were used to analyse statistically the mean differences in antioxidant properties among the fresh mango, mango powder and mango fibre. Pearson correlation test was used to analyse the correlation among the studied components at the significant level of P< 0.05. The range of antioxidant capacity as determined by FRAP, TEAC and β-carotene bleaching assay was 852.8 ± 49.2 to2000.8 ± 112.6 μmol Fe(II)/100 g edible portion (EP), 558.1 ± 78.2 to 960.8 ± 0 μg Trolox/100 g EP and 59.7 ± 1.7 to 92.2 ± 5.7 % respectively. On the other hand, total reducing activity, flavonoid, carotenoid and ascorbic acid content in the mango extracts were in the range of 122.8 ± 1.8 to 199.8 ± 5.3 mg GAE/100 g EP, 493.5 ± 33.5 to 2360.7 ± 45.7 mg catechin/100 g EP, 96.5 ± 7.6 to 153.0 ± 2.9 μg β-carotene/100 g EP and 29.4 ± 0 to 59.4 ± 0 mg ascorbic acid/100 g EP respectively. Based on one-way ANOVA test, the antioxidant capacity, total reducing activity, flavonoid, carotenoid and ascorbic acid content were significantly different (P < 0.05) among all mango extracts. The FRAP and TEAC values were in the order of fresh mango > mango fibre > mango powder whereas for β- carotene bleaching assay, the order was mango fibre > mango powder > fresh mango. Total reducing activity, flavonoid and carotenoid content in mango extracts were in the order of mango fibre > fresh mango > mango powder while the ascorbic acid content in mango extracts was in the order of mango fibre > mango powder > fresh mango. Pearson correlation coefficient showed that there was a positive strong and significant correlation (r > 0.8) between FRAP assay with TEAC assay, total reducing activity, flavonoid and carotenoid content. Also, a strong and significant correlation (r = 0.95) was observed between β-carotene bleaching assay and ascorbic acid content. This study indicated that mango fibre possessed the highest antioxidant properties compared with fresh mango and mango powder.